(untitled) (Journal of Fiber Bioengineering and Informatics, 2012)
This paper aims to make a comprehensive review of measurement methods developed for evaluating fabric and garment drape. Drapemeters used for evaluating drapeability since Pierce's bending length tester are reviewed. Parameters proposed for measuring drapeability are also considered. The authors propose that using flat fabric methods does not accurately reflect the drape of fabrics when worn. The paper is a pre-cursor to a new image analysis technique which will be reported in Part 2.